Smartphone apps for the self-management of low back pain: a systematic review - Machado, Gustavo C.; Pinheiro, Marina B.; Lee, Hopin; Ahmed, Osman H.; Hendrick, Paul; Williams, Chris; Kamper, Steven J. (Springer, 2017)
Guidelines for low back pain (LBP) often recommend the use of self-management such as unsupervised exercise, booklets, and online education. Another potentially useful way for patients to self-manage LBP is by using smartphone applications (apps). However, to date, there has been no rigorous evaluation of LBP apps and no guidance for consumers on how to select high-quality, evidence-based apps. This chapter reviews smartphone apps for the self-management of LBP and evaluates their content quality and whether they recommend evidence-based interventions. This chapter shows that generally app developers are selecting interventions that are endorsed by guidelines, although their quality is low. There are many apps available for the self-management of LBP, but their effectiveness in improving patient outcomes has not been rigorously assessed. App developers need to work closely with healthcare professionals, researchers, and patients to ensure app content is accurate, evidence based, and engaging.